INNER MONOLOGUE AS ONE OF THE PSYCHOLOGICAL ASPECTS IN THE TRANLATION OF “STARRY NIGHTS.BABUR” BY C.ERMAKOVA (Ta'limning zamonaviy transformatsiyasi, 2025)
Abstract. This article is about the usage of inner monologue as direct aspect of literary psychologism in the translation. It analyses the style and method of conveying the characters’ inner feelings by the translator.